2020
DOI: 10.3389/fpubh.2020.614113
|View full text |Cite
|
Sign up to set email alerts
|

Economic and Behavioral Influencers of Vaccination and Antimicrobial Use

Abstract: Despite vast improvements in global vaccination coverage during the last decade, there is a growing trend in vaccine hesitancy and/or refusal globally. This has implications for the acceptance and coverage of a potential vaccine against COVID-19. In the United States, the number of children exempt from vaccination for “philosophical belief-based” non-medical reasons increased in 12 of the 18 states that allowed this policy from 2009 to 2017 (1). Meanwhile, the overuse and misuse of antibiotics, especially in y… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
33
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 43 publications
(38 citation statements)
references
References 175 publications
(222 reference statements)
1
33
0
1
Order By: Relevance
“…Limited economic resources are associated with conflicting life priorities that prevent individuals from prioritizing vaccination. Workers outside the home who have not yet been infected may have developed a perception of low risk from COVID-19 14,17,35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…Limited economic resources are associated with conflicting life priorities that prevent individuals from prioritizing vaccination. Workers outside the home who have not yet been infected may have developed a perception of low risk from COVID-19 14,17,35,36 .…”
Section: Discussionmentioning
confidence: 99%
“…S13 for other parameter choices). Vaccine refusal ( 23 ) may also affect the attainment of community immunity through vaccinal immunity in the longer term (see supplementary materials).…”
Section: Epidemiological Impactsmentioning
confidence: 99%
“…This is a more context-specific model that acknowledged the importance of context, society and individual and group differences in the success of a vaccination program. Studies on vaccine hesitancy have shown the significance of context-specific factors such as risk perception, social norms, group dynamics and political ideology as important determinants of vaccine hesitancy and refusal [ 39 , 40 ]. A recent study in Malaysia by Syed Alwi et al .…”
Section: Introductionmentioning
confidence: 99%